Evaluation of image quality with four positron emitters and three preclinical PET/CT systems - Teuho J; Riehakainen L; Honkaniemi A; Moisio O; Han CL; Tirri M; Liu SH; Grönroos TJ; Liu J; Wan L; Liang X; Ling YQ; et al. (SPRINGER, 2022)
Background We investigated the image quality of C-11, Ga-68, F-18 and Zr-89, which have different positron fractions, physical half-lifes and positron ranges. Three small animal positron emission tomography/computed tomography (PET/CT) systems were used in the evaluation, including the Siemens Inveon, RAYCAN X5 and Molecubes beta-cube. The evaluation was performed on a single scanner level using the national electrical manufacturers association (NEMA) image quality phantom and analysis protocol. Acquisitions were performed with the standard NEMA protocol for F-18 and using a radionuclide-specific acquisition time for C-11, Ga-68 and Zr-89. Images were assessed using percent recovery coefficient (%RC), percentage standard deviation (%STD), image uniformity (%SD), spill-over ratio (SOR) and evaluation of image quantification. Results Ga-68 had the lowest %RC (< 62%) across all systems. F-18 had the highest maximum %RC (> 85%) and lowest %STD for the 5 mm rod across all systems. For C-11 and Zr-89, the maximum %RC was close (> 76%) to the %RC with F-18. A larger SOR were measured in water with C-11 and Ga-68 compared to F-18 on all systems. SOR in air reflected image reconstruction and data correction performance. Large variation in image quantification was observed, with maximal errors of 22.73% (Zr-89, Inveon), 17.54% (Zr-89, RAYCAN) and - 14.87% (Ga-68, Molecubes). Conclusions The systems performed most optimal in terms of NEMA image quality parameters when using F-18, where C-11 and Zr-89 performed slightly worse than F-18. The performance was least optimal when using Ga-68, due to large positron range. The large quantification differences prompt optimization not only by terms of image quality but also quantification. Further investigation should be performed to find an appropriate calibration and harmonization protocol and the evaluation should be conducted on a multi-scanner and multi-center level.